Economic science and ethical neutrality: The problem of teleology - Hodgson, Bernard (Journal of business ethics, 1983)
Two disputes have continually frustrated attempts to provide a tenable method of enquiry for economic science:, Should theory construction in economics include a commitment to moral principles? Or should economic theory remain value-free?, Does the peculiar subject matter of economics demand a ‘teleological’, or a ‘mechanistic’ pattern of explanation?, It is the aim of this paper to shed light on both the preceding controversies by seeking to clarify the relation between them. In particular, it is argued via a case study of the theory of rational choice that over-simplified mechanistic constructions have distorted the normative content and applicability of economic theory., Yet still in an explosively changing world, we have a fragmented economics · One reason for this goes deep. It is the lack of a philosophical basis for economic theory. Economic life is looked upon as deliberative action, and again it is looked upon as action determined by the combination of tastes and circumstances. Which is it? Can it be both? Nobody asks, and such problems being unrecognized, the diversity of hidden assumptions creates a babel of conflicting languages!